Dimensões da ciência e tecnologia e suas interfaces na atuação do bacharel em Gerontologia - Rosario, Natalia Maria da Silva (Universidade Federal de São Carlos, 2021)
The CTS field is an area that contributes to the potential of studies, as is the case of the present one, which involves the subject of Bachelor of Gerontology and its professional performance. Recognizing the relevance of this professional in the face of population dynamics, this study aimed to analyze the social dimensions contemplated in the formation and performance of the Bachelor of Gerontology graduated by the teaching institutions University of São Paulo (USP) and Federal University of São Carlos (UFSCar) , based on the analysis of the performance present in the Pedagogical Political Project of both academic curricula from the Lattes Platform and profiles from the LinkedIn Social Network. It was a study with plurimethodological procedures, composed of documentary research and netnographic research with publicly accessible data. The skills contained in the Political Pedagogical Projects Bachelor's Degree in Gerontology are highlighted, highlighting the emphasis on the management of organizations, programs and services, as well as the expanded concept of health placed in the demands of aging, as well as intersectoral and interdisciplinary actions, with adherence to the field CTS. The emerging visibility of the Bachelor of Gerontology in sectors and work fronts aligned with the training project is evident, challenging, however, training, especially with regard to professional practices and internship fields, in the sense of prospecting demands and creating opportunities for the interdisciplinary work of the Bachelor.
Dimensions of science and technology and their interfaces in the performance of bachelor of Gerontology
Keywords: Gerontologia; Ciência, Tecnologia e Sociedade; Interdisciplinaridade; Gerontology; Science, Technology and Society; Interdisciplinarity; CIENCIAS HUMANAS